The Complexity of Body Image Following Bariatric Surgery: A Systematic Review of the Literature - Ivezaj, Valentina (Obes Rev, 2018)
Poor body image is common among individuals seeking bariatric surgery and is associated with adverse psychosocial sequelae. Following massive weight loss secondary to bariatric surgery, many individuals experience excess skin and associated concerns, leading to subsequent body contouring procedures. Little is known, however, about body image changes and associated features from pre-to post-bariatric surgery and subsequent body contouring. The objective of the present study was to conduct a comprehensive literature review of body image following bariatric surgery to help inform future clinical research and care. The articles for the current review were identified by searching PubMed and SCOPUS and references from relevant articles. A total of 60 articles examining body image post-bariatric surgery were identified and 45 did not include body contouring surgery. Overall, there was great variation in standards of reporting sample characteristics and body image terms. When examining broad levels of body image dissatisfaction, the literature suggests general improvements in certain aspects of body image following bariatric surgery; however, few studies have systematically examined various body image domains from pre-to post-bariatric surgery and subsequent body contouring surgery. In conclusion, there is a paucity of research that examines the multidimensional elements of body image following bariatric surgery.